Power Generation Expansion Planning Including Large Scale Wind Integration: A Case Study of Oman. (17th July 2013) - Malik, Arif S.; Kuba, Cornelius
Abstract : Many options can be effectively used to meet the future power needs of a country in ways which would be more economically viable, environmentally sound, and socially just. A least-cost generation expansion planning study is conducted to find the economic feasibility of large scale integration of wind farms in the main interconnected transmission system of Oman. The generation expansion planning software used is WASP which is restricted in its ability to model intermittent nature of wind. Therefore, a wind turbine is modeled as a thermal plant with high forced outage rate related to its capacity factor. The result of the study has shown that wind turbines are economically viable option in the overall least-cost generation expansion plan for the Main Interconnected System of Oman.